Left Circumflex Artery-Right Atrium Fistula Demonstrated By Transthoracic Echocardiography - Rahul Choudhary; Vijay Pathak; Vimla Kumari; Dinesh Gautam (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
Eight year-old child presented with two year history of dyspnoea on exertion. Clinical examination revealed a continuous murmur peaking in diastole. Two dimensional transthoracic echocardiography revealed a dilated left circumflex artery (LCX) in parasternal short axis view with enlarged right atrium (RA) and right ventricle (Figures 1A,B). Apical four chamber view demonstrated fistulous flow from LCX to RA (Figures 1C,D, arrows); flow travelled initially in left atrioventricular groove and then along inter-atrial septum before opening into RA near its superior wall (Movie 1).